STUDI EMPIRIS GOOD CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY DAN MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Nurul Aini; Refi Ria Rumanti (Journal of Management and Accounting, 2021)
This study aims to examine the effect of good corporate governance and corporate social responsibility mechanisms on earnings management. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. The number of samples obtained is 332 firm years. The method used in this research is quantitative method using multiple linear regression analysis technique. The results showed that the audit committee, the board of commissioners and corporate social responsibility had no effect on earnings management. Meanwhile, institutional ownership and managerial ownership have a negative effect on earnings management. This is due to the ineffectiveness of the audit committee and independent commissioners in carrying out their duties, as well as the low implementation of corporate social responsibility in the sample companies in this study. While institutional ownership and managerial ownership partially affect earnings management. This proves that institutional investors are more concerned and careful about the profitability of companies that will benefit them. Managerial investors will feel they own the company both as decision makers and as a form of accountability for every decision taken by the manager. So that the better management performance in the company and earnings management will be minimized.